A Study on the Evaluation of Field Application of High-Fluidity Concrete Containing High Volume Fly Ash - Yun-Wang Choi; Man-Seok Park; Byung-Keol Choi; Sung-Rok Oh (Advances in Materials Science and Engineering)
In the recent concrete industry, high-fluidity concrete is being widely used for the pouring of dense reinforced concrete. Normally, in the case of high-fluidity concrete, it includes high binder contents, so it is necessary to replace part of the cement through admixtures such as fly ash to procure economic feasibility and durability. This study shows the mechanical properties and field applicability of high-fluidity concrete using mass of fly ash as alternative materials of cement. The high-fluidity concrete mixed with 50% fly ash was measured to manufacture concrete that applies low water/binder ratio to measure the mechanical characteristics as compressive strength and elastic modulus. Also, in order to evaluate the field applicability, high-fluidity concrete containing high volume fly ash was evaluated for fluidity, compressive strength, heat of hydration, and drying shrinkage of concrete.